2016
DOI: 10.1016/j.jhsa.2016.07.098
|View full text |Cite
|
Sign up to set email alerts
|

A Cadaveric Study for the Improvement of Thread Carpal Tunnel Release

Abstract: The modified TCTR has the potential to offer a clinically safe and effective minimally invasive procedure for complete carpal tunnel release.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
40
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 33 publications
(42 citation statements)
references
References 20 publications
2
40
0
Order By: Relevance
“…In a recent study on 11 unembalmed cadaveric wrists, the modified TCTR procedure was verified and the needle control accuracy was measured to be 0.15 to 0.2 mm, which is precise enough to protect the superficial palmar aponeurosis (SupPA), Berrettini branch, and common digital nerves. 14 …”
Section: Introductionmentioning
confidence: 99%
“…In a recent study on 11 unembalmed cadaveric wrists, the modified TCTR procedure was verified and the needle control accuracy was measured to be 0.15 to 0.2 mm, which is precise enough to protect the superficial palmar aponeurosis (SupPA), Berrettini branch, and common digital nerves. 14 …”
Section: Introductionmentioning
confidence: 99%
“…The cutting wire has been previously studied for other USG surgical procedures. Prior cadaveric and clinical investigations have demonstrated that USG cutting wire releases for carpal tunnel syndrome and trigger fingers are safe and effective 15,16,21–23 . We recently completed a study demonstrating the feasibility of an USG adductor longus tendon release using a cutting wire 14 .…”
Section: Discussionmentioning
confidence: 99%
“…Initially, US was used for simple procedures, such as USG joint, bursa, and tendon sheath injections. More recently, advanced needle based procedures (eg, needle tenotomy) and USG surgical procedures (compartment fasciotomies, ultrasonic tendon debridement, carpal tunnel releases, adductor longus releases, long head of the biceps tendon releases) have been introduced into orthopedic and sports medicine settings 13–19 . USG procedures may offer the benefit of lower risk, less pain, quicker recovery, and lower cost when compared to open surgical procedures 20 .…”
Section: Introductionmentioning
confidence: 99%
“…In the accompanying figures, the indication of the distal part of the duck's beak shows a short, tapered end, which is unclear in the accompanying US image. Guo et al subsequently defined their concept of the duck's beak with an elongated distal segment superficial to the fat pad enclosing the distal transverse carpal ligament, describing this appearance as the blending of the ligament with the palmar aponeurosis. The subsequent diagram of the position of their cutting thread excluded this elongated distal segment, which represented the palmar aponeurosis alone.…”
Section: Discussionmentioning
confidence: 99%
“…To be described as microinvasive, a procedure needs to be performed without incisions: that is, with 14‐gauge (2.1‐mm) or smaller needle‐sized instruments that will not leave a notable scar. Microinvasive approaches to cutting the transverse carpal ligament have been described, including an abrading saw with entry and exit holes and a cutting thread or wire, threaded through a needle from the palm to a wrist exit hole and then back again to encircle and cut the transverse carpal ligament while preserving the palmar aponeurosis . Simple repeated needle fenestration of the transverse carpal ligament has also been described …”
mentioning
confidence: 99%